The Role of Agents in Marketing Perspective (Post Implementation Study of Branchless Banking in Mandiri Bank Semarang Pahlawan Area) - Indra Septa Widiarta; Mirwan Surya Perdhana (Budapest International Research and Critics University, 2022)
The research was conducted to examine the public's perception of the existence of Bank Mandiri agents in the Pahlawan area after the implementation of the branchless banking program, the effectiveness of agents, and the various challenges faced. The research was conducted with a qualitative design with 3 (three) sources of informants, namely the community (33 people), agents (20 people), and the management of Bank Mandiri in the Hero area (8 people). Based on the data that has been collected, then an analysis is carried out using qualitative techniques. The results of the study show the concept that: (1). Age 17-40 years has the potential to be 52%, high school education level/equivalent is possible 55%, private sector employment 58%, and length of time being a customer 2-10 years 56% are predicted to be able to influence public interest in using agent services. People who have/have used agent services have not been able to generate interest in transacting again in the future by up to 57%. (2). The development of agent performance in quadrant D at Region VII level in 2021 is effective, ranking 2 with the best performance achievement. Quadrant E is not yet effective because it is ranked 6th bottom out of 8 work areas. (3). The toughest internal challenge faced is the demand to prioritize the precautionary principle, and to prioritize the principle of obedience to various regulations. Limited cash reserves and agent capabilities are considered the strongest external challenges.